Prevalence of depression amongst caregivers of stroke patients attending Hospital Universiti Sains Malaysia - Abdul Hadi, Azwanis; Pasi, Hafizah; Abd Alla Yousseff, Nivin Essameldin (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
Introduction: Caregiving for stroke patients is a challenging task both emotionally and physically. Studies have shown that caregiving can affect caregivers’ wellbeing that could lead to depression. Objective: This study was carried out to determine the prevalence and associated risk factors of depression amongst caregivers of stroke patients attending Hospital Universiti Sains Malaysia (HUSM) in Kelantan over a 6 month period. Methodology: This is a cross sectional study at the primary care clinic in HUSM over a period of 6 months. A total of 116 caregivers of medically documented stroke patients who fulfilled the inclusion and exclusion criteria were recruited via convenience sampling. The brief patient health questionnaire (PHQ-9) were used to assess their depression. Descriptive statistics and bivariable analysis was used using SPSS version 23.Results: 63.8% of the caregivers of stroke patients are depressed. Caregiver’s burden, ethnicity and patient’s ethnicity were found to be significant associated risk factors for depression.Conclusion: Screening for depression in caregivers especially those with risk factors must be carried out in the clinic in order to detect and intervene early. Coping mechanisms especially in the religious aspect should be elicited in future studies.